Public sector innovation : The role of commercial partnerships - Baxter, David; Schoeman, Magnus; Goffin, Keith; Micheli, Pietro (Cranfield University School of Management, 2010)
The global economic situation is putting increasing pressure on public sector funding and so innovation is now being recognised as an essential mechanism for maintaining the quality and scope of services whilst reducing costs. This report describes new research into a specific type of public sector innovation – commercialisation: partnerships between the public sector and commercial organisations which enable new or enhanced services to be developed. A crucial aspect of such partnerships is that they can lead to the development of new services which create new value. This enables financial and other benefits for both the public sector and commercial partners. The research conducted for this report consisted of a survey of civil servants’ views on commercialisation and two case studies of successful innovation—the Public Sector Broadband Aggregation (PSBA) in Wales and the Met Office Healthy Outlook ® service. The survey enabled barriers to commercialisation to be identified, such as lack of guidance and support, lack of clarity in the remit of the public sector, and inadequate awareness of the opportunities. The two case studies enabled the key characteristics of commercialisation to be determined, particularly the need to start early discussions with potential commercial partners, to gain board level sponsorship for projects, and to ensure that the value of the innovation is shared. Contrasting the results of our research to the way innovation is managed in the private sector, allows us to make four main recommendations on maximising the value of commercial partnerships: - The focus of public sector innovation must go beyond service efficiency, and the exploitation of internally generated ideas. To gain the maximum value from public sector assets, suitable discussions need to be held with potential commercial partners. - Discussions with the commercial sector have the potential to create innovative ideas for new services. The public sector will need to become adept at conducting early stage discussions with commercial organisations, if it is to gain the maximum value from public assets. Suitable partners need to be identified, where the capabilities of the commercial sector complement the unique expertise and assets of the public sector. Making such partnerships work will require trust on both sides and sharing of the value generated from the innovation developed. - Managers in the public sector urgently require more guidance and support on how to apply the concept of commercialisation and achieve the benefits. - Public sector innovation is very different from innovation in the commercial sector. Therefore, although there are some points to be learned from the commercial sector, appropriate tools need to be developed for the public sector and these need to be disseminated to civil servants.